Flexible glass and preparation method thereof
By using technical means such as slit pull-down, cutting thinning, nanotitanium dioxide and potassium hydroxide reaction deposition during the preparation of flexible glass, combined with electrostatic self-assembly and vacuum impregnation, a crosslinking network structure is formed, which solves the problems of insufficient mechanical properties and other performance of flexible glass, and achieves higher UV resistance, impact resistance and peel resistance.
Patent Information
- Application Number
- CN202210574203.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-05-24
AI Technical Summary
Existing flexible glass has shortcomings in mechanical properties and other properties, and it is difficult to meet higher application needs.
Modified glass is prepared through steps such as slit pulling, cutting thinning, nanotitanium dioxide and potassium hydroxide reaction deposition, plasma treatment, electrostatic self-assembly and vacuum impregnation, and a crosslinking network structure is formed through multi-stage heat treatment to improve the mechanical properties and peel resistance of the glass.
It significantly improves the UV resistance, impact resistance and peel resistance of flexible glass, and meets higher mechanical and chemical performance requirements.
Smart Images

Figure BDA0003660042610000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flexible glass, in particular to flexible glass and a preparation method thereof. Background Art
[0002] Flexible glass refers to ultra-thin glass with a thickness of ≤0.1mm. Compared with glass that is thinned by grinding and polishing, flexible glass can be directly drawn and formed, which can achieve continuous production. The drawn glass can be rolled up like a plastic film, which makes it possible to realize the "roll-to-roll" process. Flexible glass can be bent, and at the same time has the hardness, transparency, heat resistance, electrical insulation, airtightness and stable mechanical and chemical properties of glass in oxidation and light environments.
[0003] With the advancement of science and technology and the development of society, the development of ultra-thin displays, curved screens, and glass protective films has made flexible glass have a broad market and is widely used in the electronics industry, especially the information industry. However, due to its small thickness, its mechanical properties and other properties are also reduced. How to make flexible glass have better mechanical properties and other properties is an aspect of research. Summary of the invention
[0004] The object of the present invention is to provide a flexible glass and a preparation method thereof to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing flexible glass, characterized in that the flexible glass is prepared by slit-drawing and cutting glass liquid, reacting and depositing nano-titanium dioxide and potassium hydroxide, and plasma-treating the glass to obtain modified glass, electrostatically assembling the modified glass with polyamic acid, and then vacuum-impregnating the modified cage-type polysilsesquioxane and subjecting the glass to multi-stage heat treatment.
[0007] As an optimization, the polyamic acid is prepared by reacting 5-vinylisophthalic acid, p-phenylenediamine and triethoxysilane to obtain triphenylamide triethoxysilane, and biphenyltetracarboxylic acid dianhydride, 3,5-diaminobenzoic acid ethyl ester and triphenylamide triethoxysilane to obtain the polyamic acid.
[0008] As an optimization, the modified cage-type polysilsesquioxane is prepared by self-polymerization of vinyltrimethoxysilane to obtain cage-type polysilsesquioxane, which is prepared by reacting the cage-type polysilsesquioxane with hydrogen-containing silicone oil and then reacting with vinyltrimethoxysilane.
[0009] As an optimization, the method for preparing the flexible glass includes the following preparation steps:
[0010] (1) Slit drawing: Cooling the glass liquid to 1400-1450°C, performing slit drawing, the slit temperature is 1280-1300°C, the air temperature is 700-750°C, the slit width is 2-2.5 mm, the drawing speed is 15-25 mm / s, and then placed in a room temperature environment for 10-12 hours to obtain a semi-finished glass;
[0011] (2) Cutting and thinning: soak the semi-finished glass in an acid solution for 3 to 5 minutes, take it out and wash it with pure water for 3 to 5 times, dry it at 60 to 70°C for 4 to 6 hours, and then cut it to the required size with a femtosecond laser. The femtosecond laser pulse width is 100 to 300 fs. The cut semi-finished glass is suspended and soaked in an acid solution, and ultrasonicated at 20 to 30°C and 30 to 40 kHz for 15 to 20 minutes. Take it out and wash it with pure water for 3 to 5 times, and dry it at 60 to 70°C for 4 to 6 hours to obtain glass;
[0012] (3) Deposition and plasma treatment: TEOS solution was sprayed at 0.05-0.08 g / cm 2 The amount of the sprayed glass is sprayed on the surface of one side of the glass, and the glass is allowed to stand at 60-70°C for 30-40 minutes to obtain the sprayed glass; the sprayed surface of the sprayed glass is fixed on the bottom of the container with the sprayed surface facing upward, and then nano titanium dioxide and potassium hydroxide with a mass fraction of 50-60% are mixed and evenly added in a mass ratio of 1:6-1:8, and the distance from the liquid surface to the sprayed glass surface is 2-3 cm, and the reaction is carried out at 180-200°C for 4-5 hours, and the glass is taken out after cooling to room temperature and washed with pure water for 3-5 times, and then dried at 100-120°C for 2-3 hours, and then allowed to stand at 500-600°C for 6-8 hours in a nitrogen atmosphere, and the glass is placed in a cavity of a hydrogen plasma treatment instrument with the surface facing upward. After the vacuum pump is evacuated to a vacuum degree of 5-10Pa, hydrogen is introduced to a vacuum degree of 70-80Pa, and hydrogen plasma treatment is carried out. The hydrogen plasma treatment power is 100-200W, and the treatment time is 10-15min to obtain modified glass;
[0013] (4) Electrostatic self-assembly: Biphenyltetracarboxylic acid anhydride, 3,5-diaminobenzoic acid ethyl ester, triphenylamide triethoxysilane and dimethylacetamide are mixed uniformly in a mass ratio of 5:1:3:40 to 5:2:2:50, stirred at 800 to 1000 r / min for 20 to 24 h in a nitrogen atmosphere at 5 to 15 ° C, and then 50 to 60% ethanol with a mass fraction of 40 to 50 times the mass of biphenyltetracarboxylic acid anhydride is added, and stirring is continued for 10 to 15 min to obtain a polyamic acid solution; the modified glass is immersed in the polyamic acid solution, ultrasonicated at 20 to 30 ° C, 30 to 40 kHz for 20 to 30 min, washed with anhydrous ethanol for 3 to 5 times, and dried at 60 to 70 ° C for 4 to 6 h to obtain an electrostatic self-assembled glass;
[0014] (5) Vacuum impregnation: The modified cage-type polysilsesquioxane, acetone and 70-80% ethanol by mass were mixed uniformly in a mass ratio of 1:4:4 to 1:6:6, and stirred at 20-30°C and 300-500 r / min for 2-3 min to prepare an impregnation solution; the electrostatic self-assembled glass was immersed in a hydrochloric acid solution with a mass fraction of 8-10%, and ultrasonicated at 20-30°C and 30-40 kHz for 8-10 min, and dried at -10--1°C and 1-10 Pa for 6-8 h, and then fix it in a vacuum impregnation machine with the assembled surface facing upward, pump the pressure to 1-10Pa, then add impregnation liquid that is 3-4 times the mass of the electrostatic self-assembled glass, and then introduce nitrogen to make the pressure reach 10-20kPa. Let it stand at 10-20℃ for 30-40min, rinse the assembled surface with anhydrous ethanol and pure water for 3-5min respectively, dry it at -1--10℃ and 1-10Pa for 6-8h, let it stand at 140-150℃ for 2-3h, and then perform multiple-stage heat treatment to obtain flexible glass.
[0015] As an optimization, the glass liquid in step (1) is prepared by uniformly mixing silicon dioxide, aluminum oxide, magnesium oxide, calcium oxide, boron trioxide, strontium oxide, tin oxide, and yttrium oxide in a mass ratio of 90:20:3:1:2:2:0.3:1 to 120:30:5:3:4:3:0.5:3 and placing the mixture in a platinum crucible, standing at 800 to 1000° C. for 15 to 20 minutes, and then heating the mixture to 1600 to 1800° C. and standing the mixture for 2 to 3 hours.
[0016] As an optimization, the acid solution in step (2) is prepared by uniformly mixing hydrofluoric acid with a mass fraction of 6 to 10% and hydrochloric acid with a mass fraction of 15 to 25% in a mass ratio of 1:1 to 1:2.
[0017] As an optimization, the tetraethyl orthosilicate solution in step (3) is prepared by uniformly mixing tetraethyl orthosilicate, anhydrous ethanol and pure water in a mass ratio of 1:4:4 to 1:6:6, and stirring at 20 to 30° C. and 300 to 500 r / min for 2 to 3 minutes.
[0018] As an optimization, the preparation method of the triphenylamide triethoxysilane in step (4) is as follows: 5-vinylisophthalic acid, p-phenylenediamine, pure water and anhydrous ethanol are uniformly mixed in a mass ratio of 1:4:8:8 to 1:5:10:10, and then 0.01 to 0.03 times the mass of 5-vinylisophthalic acid is added with carbodiimide, and the mixture is stirred at 20 to 30°C and 800 to 1000 r / min for 2 to 3 hours, and the mixture is heated at 30 to 40°C. ℃, 1-2kPa and stand for 8-10h to obtain triphenylamide; triphenylamide, triethoxysilane and n-hexane are uniformly mixed in a mass ratio of 1:1:8-1:2:10, and then 0.03-0.05 of divinyltetramethyldisiloxane platinum salt by mass of triphenylamide is added, and refluxed with stirring at 70-80℃, 500-800r / min for 4-6h, and stand at 20-30℃, 1-2kPa for 3-4h to prepare it.
[0019] As an optimization, the preparation method of the modified cage-type polysilsesquioxane in step (5) is as follows: vinyl trimethoxysilane, hydrochloric acid with a mass fraction of 25 to 30% and anhydrous ethanol are uniformly mixed in a mass ratio of 1:1:10 to 1:2:15, stirred at 20 to 30°C and 1500 to 2000 r / min for 4 to 6 hours, cooled to 1 to 5°C, filtered, and washed with pure water and anhydrous ethanol for 3 to 5 times respectively, and dried at 60 to 70°C and 5 to 10 Pa for 6 to 8 hours to obtain a cage-type polysilsesquioxane; the cage-type polysilsesquioxane is Siloxane and hydrogen-containing silicone oil are uniformly mixed in a mass ratio of 1:6 to 1:8, and then chloroplatinic acid with a mass of 0.003 to 0.005 times the mass of cage-type polysilsesquioxane is added, and the mixture is stirred at 70 to 80°C and 500 to 800 r / min for 10 to 15 minutes, and then the temperature is raised to 100 to 110°C and stirring is continued for 4 to 6 hours, and then vinyltrimethoxysilane with a mass of 2 to 3 times the mass of cage-type polysilsesquioxane is added, and stirring is continued for 4 to 6 hours while keeping the temperature unchanged, and the mixture is allowed to stand at 40 to 50°C and 1 to 2 kPa for 8 to 10 hours to prepare the product.
[0020] As an optimization, the method of the multi-stage heat treatment in step (5) is: standing at 200-250°C for 1-2 hours, standing at 350-400°C for 1-2 hours, with a heating rate of 2-3°C / min, and cooling to room temperature.
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] When preparing the flexible glass, the present invention firstly performs slit-drawing and cutting on the glass liquid, deposits nano-titanium dioxide and potassium hydroxide through reaction and plasma treatment to obtain the modified glass, electrostatically assembles the modified glass with polyamic acid, and then performs vacuum impregnation with modified cage-type polysilsesquioxane and multi-stage heat treatment to obtain the flexible glass.
[0023] Firstly, nano-titanium dioxide and potassium hydroxide react and deposit on the glass surface to form potassium titanate whiskers, which have the effect of strengthening and toughening the main body, and can absorb, reflect and scatter ultraviolet radiation, thereby improving the ultraviolet protection and impact resistance of the flexible glass; after hydrogen plasma treatment, oxygen defects are generated on the treated glass surface, and the modified glass surface is positively charged during the electrostatic self-assembly process, and the negatively charged polyamic acid is electrostatically adsorbed on the surface to form an electrostatic self-assembly layer, thereby improving the peeling resistance of the flexible glass; 5-vinyl isophthalic acid and p-phenylenediamine are reacted and then reacted with triethoxysilane to obtain triphenylamide triethoxysilane, and biphenyltetracarboxylic acid dianhydride, 3,5-diaminobenzoic acid ethyl ester, and triphenylamide triethoxysilane are reacted to obtain polyamic acid, and while the polyamic acid is electrostatically adsorbed on the surface during the electrostatic self-assembly process, the triphenylamide triethoxysilane is hydrolyzed to produce silanol groups and forms a chemical bond with the modified glass, thereby improving the peeling resistance of the flexible glass.
[0024] Secondly, vinyl trimethoxysilane is self-polymerized to obtain cage-type polysilsesquioxane, and the cage-type polysilsesquioxane is reacted with hydrogen-containing silicone oil and then reacted with vinyl trimethoxysilane to obtain modified cage-type polysilsesquioxane, which increases the fluidity of the cage-type polysilsesquioxane, and the flexible side chains can combine with the hydrolyzed silanol groups on the electrostatic self-assembled layer to form a cross-linked network structure, increase the elasticity of the material, and fix the cage-type polysilsesquioxane in the overall structure as a stress node, thereby improving the peeling resistance and impact resistance of the flexible glass; multi-stage heat treatment forms polyimide, increases the overall conjugated structure, is easier to absorb ultraviolet rays and form mobile electrons, thereby improving the ultraviolet protection of the flexible glass, and makes the free silanol groups react with each other to form silicon-oxygen connections, making the overall structure tighter, thereby improving the peeling resistance of the flexible glass, and generating polyimide at the same time. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe the method in detail. The test methods of various indicators of the flexible glass prepared in the following examples are as follows:
[0027] Anti-ultraviolet performance: The flexible glass obtained in each embodiment and the comparative example material were taken with the same size, shape and thickness, and the ultraviolet transmittance was tested according to the GB / T2680 standard method.
[0028] Peeling resistance: The flexible glass obtained in each embodiment and the comparative example material were taken with the same size, shape and thickness, and the peeling strength was tested according to the GB / T8808 standard method.
[0029] Impact resistance: The flexible glass obtained in each embodiment and the comparative example material were taken with the same size, shape and thickness, and the impact strength was tested according to the GB / T39814 standard method.
[0030] Example 1
[0031] A method for preparing flexible glass, the method for preparing flexible glass mainly comprises the following preparation steps:
[0032] (1) Slit drawing: Silicon dioxide, aluminum oxide, magnesium oxide, calcium oxide, boron trioxide, strontium oxide, tin oxide, and yttrium oxide are mixed uniformly in a mass ratio of 90:20:3:1:2:2:0.3:1 and placed in a platinum crucible, allowed to stand at 800°C for 20 minutes, then heated to 1600°C and allowed to stand for 3 hours to obtain glass liquid; the glass liquid is cooled to 1400°C and slit drawn, with a slit temperature of 1280°C, an air temperature of 700°C, a slit width of 2 mm, and a pull-down speed of 15 mm / s, and then allowed to stand at room temperature for 12 hours to obtain semi-finished glass;
[0033] (2) Cutting and thinning: 6% by mass hydrofluoric acid and 15% by mass hydrochloric acid are mixed in a mass ratio of 1:1 to prepare an acid solution. The semi-finished glass is placed in the acid solution and soaked for 3 minutes. The semi-finished glass is taken out and washed with pure water for 3 times, dried at 60°C for 6 hours, and then cut to the required size with a femtosecond laser. The femtosecond laser pulse width is 100 fs. The cut semi-finished glass is suspended and soaked in the acid solution. Ultrasonic treatment is carried out at 20°C and 30kHz for 20 minutes. The semi-finished glass is taken out and washed with pure water for 3 times, and dried at 60°C for 6 hours to obtain glass.
[0034] (3) Deposition and plasma treatment: TEOS, anhydrous ethanol and pure water were mixed evenly in a mass ratio of 1:4:4, stirred at 20°C and 300 r / min for 3 min to obtain a TEOS solution. The TEOS solution was sprayed at 0.05 g / cm 2spraying the glass on one side of the glass, standing at 60°C for 40 minutes to obtain the sprayed glass; fixing the sprayed surface of the sprayed glass on the bottom of the container with the sprayed surface facing upward, and then mixing nano titanium dioxide and potassium hydroxide with a mass fraction of 50% in a mass ratio of 1:6 and adding them evenly, and making the distance from the liquid surface to the sprayed glass surface be 2 cm, reacting at 180°C for 5 hours, taking out after cooling to room temperature and washing with pure water for 3 times, drying at 100°C for 3 hours, and then standing at 500°C for 8 hours in a nitrogen atmosphere, keeping it facing upward and placing it in the cavity of a hydrogen plasma treatment instrument, evacuating the vacuum pump to make the vacuum degree reach 5Pa, and then introducing hydrogen to make the vacuum degree reach 70Pa, and performing hydrogen plasma treatment, the hydrogen plasma treatment power is 100W, and the treatment time is 15 minutes, to obtain modified glass;
[0035] (4) Electrostatic self-assembly: 5-vinylisophthalic acid, p-phenylenediamine, pure water and anhydrous ethanol were mixed in a mass ratio of 1:4:8:8, and then 0.01 times the mass of 5-vinylisophthalic acid was added with carbodiimide, stirred at 20°C, 800 r / min for 3 h, and allowed to stand at 30°C, 1 kPa for 10 h to obtain triphenylamide; triphenylamide, triethoxysilane and n-hexane were mixed in a mass ratio of 1:1:8, and then 0.03-0.05 times the mass of triphenylamide was added with divinyltetramethyldisiloxane platinum salt, stirred and refluxed at 70°C, 500 r / min for 6 h, and allowed to stand at 20°C, 1 kPa for 10 h. a was allowed to stand for 4 hours to obtain triphenylamide triethoxysilane; biphenyltetracarboxylic acid dianhydride, 3,5-diaminobenzoic acid ethyl ester, triphenylamide triethoxysilane and dimethylacetamide were mixed evenly in a mass ratio of 5:1:3:40, stirred at 5°C and 800r / min for 24 hours in a nitrogen atmosphere, and then 50% ethanol with a mass fraction of 40 times the mass of biphenyltetracarboxylic acid dianhydride was added, and the stirring was continued for 10 minutes to obtain a polyamic acid solution; the modified glass was immersed in the polyamic acid solution, ultrasonicated at 20°C and 30kHz for 30 minutes, washed with anhydrous ethanol 3 times, and dried at 60°C for 6 hours to obtain an electrostatic self-assembled glass;
[0036] (5) Vacuum impregnation: Vinyl trimethoxysilane, 25% hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:1:10, stirred at 20°C and 1500 r / min for 6 h, cooled to 1°C, filtered, washed with pure water and anhydrous ethanol 3 times each, and dried at 60°C and 5 Pa for 8 h to obtain cage-type polysilsesquioxane; cage-type polysilsesquioxane and hydrogen-containing silicone oil were mixed in a mass ratio of 1:6, and 0.003 times the mass of cage-type polysilsesquioxane was added with chloroplatinic acid, stirred at 70°C and 500 r / min for 15 min, then heated to 100°C and stirred for 6 h, and then vinyl trimethoxysilane was added in an amount of 2 times the mass of cage-type polysilsesquioxane, the temperature was kept constant and stirred for 4 h, and then allowed to stand at 40°C and 1 kPa for 10 h to obtain modified cage-type polysilsesquioxane; modified cage-type polysilsesquioxane was mixed in a mass ratio of 1:6, and 0.003 times the mass of cage-type polysilsesquioxane was added with chloroplatinic acid, stirred at 70°C and 500 r / min for 15 min, then heated to 100°C and stirred for 6 h, then 2 times the mass of cage-type polysilsesquioxane was added with vinyl trimethoxysilane, stirred at the same temperature for 4 h, and allowed to stand at 40°C and 1 kPa for 10 h to obtain modified cage-type polysilsesquioxane; Silsesquioxane, acetone and 70% ethanol by mass were mixed uniformly in a mass ratio of 1:4:4, stirred at 20°C and 300r / min for 3min to prepare an impregnation solution; the electrostatic self-assembled glass was immersed in a hydrochloric acid solution with a mass fraction of 8%, ultrasonicated at 20°C and 30kHz for 10min, dried at -10°C and 1Pa for 8h, and then fixed in a vacuum impregnation machine with the assembled surface facing upward, and after the pressure was pumped to 1Pa, an impregnation solution 3 times the mass of the electrostatic self-assembled glass was added, and nitrogen was introduced to make the pressure reach 10kPa, and the assembled glass was allowed to stand at 10°C for 40min, and the assembled surface was rinsed with anhydrous ethanol and pure water for 3min respectively, and dried at -1°C and 1Pa for 8h, and allowed to stand at 140°C for 2h, at 200°C for 1h, and at 350°C for 1h. The heating rate was 2°C / min, and the glass was cooled to room temperature to obtain a flexible glass.
[0037] Example 2
[0038] A method for preparing flexible glass, the method for preparing flexible glass mainly comprises the following preparation steps:
[0039] (1) Slit drawing: Silicon dioxide, aluminum oxide, magnesium oxide, calcium oxide, boron trioxide, strontium oxide, tin oxide, and yttrium oxide are mixed uniformly in a mass ratio of 115:25:4:2:3:2.5:0.4:2 and placed in a platinum crucible, and allowed to stand at 900°C for 18 minutes, and then heated to 1700°C and allowed to stand for 2.5 hours to obtain glass liquid; the glass liquid is cooled to 1420°C and slit drawn, with a slit temperature of 1290°C, an air temperature of 720°C, a slit width of 2.53m, and a pull-down traction speed of 20m / s, and then allowed to stand at room temperature for 11 hours to obtain semi-finished glass;
[0040] (2) Cutting and thinning: 8% by mass hydrofluoric acid and 20% by mass hydrochloric acid were mixed in a mass ratio of 1:1.5 to prepare an acid solution. The semi-finished glass was placed in the acid solution and soaked for 4 minutes. The semi-finished glass was taken out and washed with pure water for 4 times, dried at 65°C for 5 hours, and then cut to the required size with a femtosecond laser. The femtosecond laser pulse width was 200fs. The semi-finished glass after cutting was suspended and soaked in the acid solution. Ultrasonic treatment was performed at 25°C and 35kHz for 18 minutes. The semi-finished glass was taken out and washed with pure water for 4 times, and dried at 65°C for 5 hours to obtain glass.
[0041] (3) Deposition and plasma treatment: TEOS, anhydrous ethanol and pure water were mixed evenly in a mass ratio of 1:5:5, stirred at 25°C and 40 r / min for 2.5 min to obtain a TEOS solution. The TEOS solution was sprayed at a rate of 0.06 g / cm 2 The amount of the sprayed glass was sprayed on the surface of one side of the glass, and the glass was allowed to stand at 65°C for 35 minutes to obtain the sprayed glass; the sprayed surface of the sprayed glass was fixed upward at the bottom of the container, and then nano titanium dioxide and potassium hydroxide with a mass fraction of 55% were mixed and evenly added in a mass ratio of 1:7, and the distance from the liquid surface to the sprayed glass surface was 2.5 cm, and the reaction was carried out at 190°C for 4.5 hours, and the glass was taken out after cooling to room temperature and washed with pure water for 4 times, and then dried at 110°C for 2.5 hours, and then allowed to stand at 550°C for 7 hours in a nitrogen atmosphere, and the glass was kept facing upward and placed in the cavity of a hydrogen plasma treatment instrument. The vacuum pump was evacuated to a vacuum degree of 8Pa, and then hydrogen was introduced to a vacuum degree of 75Pa, and hydrogen plasma treatment was carried out. The hydrogen plasma treatment power was 150W, and the treatment time was 12 minutes to obtain modified glass;
[0042] (4) Electrostatic self-assembly: 5-vinylisophthalic acid, p-phenylenediamine, pure water and anhydrous ethanol were mixed in a mass ratio of 1:4.5:9:9, and then 0.02 times the mass of 5-vinylisophthalic acid carbodiimide was added, and the mixture was stirred at 25°C and 900 r / min for 2.5 h, and then allowed to stand at 35°C and 1.5 kPa for 9 h to obtain triphenylamide; triphenylamide, triethoxysilane and n-hexane were mixed in a mass ratio of 1:1.5:9, and then 0.03-0.05 times the mass of triphenylamide divinyltetramethyldisiloxane platinum salt was added, and the mixture was stirred and refluxed at 75°C and 650 r / min for 5 h, and then allowed to stand at 25°C and 1.5 kPa for 9 h. Pa was allowed to stand for 3.5 hours to obtain triphenylamide triethoxysilane; biphenyltetracarboxylic acid dianhydride, 3,5-diaminobenzoic acid ethyl ester, triphenylamide triethoxysilane and dimethylacetamide were mixed evenly in a mass ratio of 5:1.5:2.5:45, stirred at 10°C and 900r / min for 22 hours in a nitrogen atmosphere, and then 55% ethanol with a mass fraction of 45 times the mass of biphenyltetracarboxylic acid dianhydride was added, and stirring was continued for 12 minutes to obtain a polyamic acid solution; the modified glass was immersed in the polyamic acid solution, ultrasonicated at 25°C and 35kHz for 25 minutes, washed with anhydrous ethanol 4 times, and dried at 65°C for 5 hours to obtain an electrostatic self-assembled glass;
[0043] (5) Vacuum impregnation: Vinyl trimethoxysilane, 28% hydrochloric acid and anhydrous ethanol were mixed in a mass ratio of 1:1.5:12, stirred at 25°C and 1800 r / min for 5 h, cooled to 3°C, filtered, washed with pure water and anhydrous ethanol 4 times each, and dried at 65°C and 8 Pa for 7 h to obtain cage-type polysilsesquioxane; cage-type polysilsesquioxane and hydrogen-containing silicone oil were mixed in a mass ratio of 1:7, and 0.004 times the mass of cage-type polysilsesquioxane was added with chloroplatinic acid, stirred at 75°C and 650 r / min for 12 min, then heated to 105°C and stirred for 5 h, and then 2.5 times the mass of cage-type polysilsesquioxane was added with vinyl trimethoxysilane, the temperature was kept constant and stirred for 5 h, and then allowed to stand at 45°C and 1.5 kPa for 9 h to obtain modified cage-type polysilsesquioxane; the modified cage-type polysilsesquioxane was mixed with hydrogen-containing silicone oil in a mass ratio of 1:7, and then 0.004 times the mass of cage-type polysilsesquioxane was added with chloroplatinic acid, stirred at 75°C and 650 r / min for 12 min, then heated to 105°C and stirred for 5 h, then 2.5 times the mass of cage-type polysilsesquioxane was added with vinyl trimethoxysilane, the temperature was kept constant and stirred for 5 h, and then allowed to stand at 45°C and 1.5 kPa for 9 h to obtain modified cage-type polysilsesquioxane; The oxane, acetone and 75% ethanol by mass were mixed uniformly in a mass ratio of 1:5:5, stirred at 25°C and 400r / min for 2.5min to prepare an impregnation solution; the electrostatic self-assembled glass was immersed in a 9% hydrochloric acid solution by mass, ultrasonicated at 25°C and 35kHz for 9min, dried at -5°C and 5Pa for 7h, and then fixed in a vacuum impregnation machine with the assembled surface upward, and after the pressure was pumped to 5Pa, an impregnation solution 3.5 times the mass of the electrostatic self-assembled glass was added, and nitrogen was introduced to make the pressure reach 15kPa, and the glass was allowed to stand at 15°C for 35min, and the assembled surface was rinsed with anhydrous ethanol and pure water for 4min respectively, and dried at -8°C and 5Pa for 7h, and then allowed to stand at 145°C for 2.5h, at 230°C for 1.5h, and at 380°C for 1.5h, with a heating rate of 2.5°C / min, and cooled to room temperature to obtain flexible glass.
[0044] Example 3
[0045] A method for preparing flexible glass, the method for preparing flexible glass mainly comprises the following preparation steps:
[0046] (1) Slit drawing: Silicon dioxide, aluminum oxide, magnesium oxide, calcium oxide, boron trioxide, strontium oxide, tin oxide, and yttrium oxide are mixed uniformly in a mass ratio of 120:30:5:3:4:3:0.5:3 and placed in a platinum crucible, and allowed to stand at 1000°C for 15 minutes, and then heated to 1800°C and allowed to stand for 2 hours to obtain glass liquid; the glass liquid is cooled to 1450°C and slit drawn, with a slit temperature of 1300°C, an air temperature of 750°C, a slit width of 2.5 mm, and a pull-down traction speed of 25 mm / s, and then allowed to stand at room temperature for 12 hours to obtain semi-finished glass;
[0047] (2) Cutting and thinning: 10% by mass hydrofluoric acid and 25% by mass hydrochloric acid are mixed in a mass ratio of 1:2 to prepare an acid solution. The semi-finished glass is placed in the acid solution and soaked for 5 minutes. The semi-finished glass is taken out and washed with pure water for 5 times, dried at 70°C for 5 hours, and then cut to the required size with a femtosecond laser. The femtosecond laser pulse width is 300fs. The cut semi-finished glass is suspended and soaked in the acid solution. Ultrasonic treatment is carried out at 30°C and 40kHz for 15 minutes. The semi-finished glass is taken out and washed with pure water for 5 times, and dried at 70°C for 4 hours to obtain glass.
[0048] (3) Deposition and plasma treatment: TEOS, anhydrous ethanol and pure water were mixed evenly in a mass ratio of 1:6:6, stirred at 30°C and 500 r / min for 2 min to obtain a TEOS solution. The TEOS solution was sprayed at 0.08 g / cm 2 The amount of the sprayed glass was sprayed on the surface of one side of the glass, and the glass was allowed to stand at 70°C for 30 minutes to obtain the sprayed glass; the sprayed surface of the sprayed glass was fixed on the bottom of the container with the sprayed surface facing upward, and then nano titanium dioxide and potassium hydroxide with a mass fraction of 60% were mixed and evenly added in a mass ratio of 1:8, and the distance from the liquid surface to the sprayed glass surface was 3 cm, and the reaction was carried out at 200°C for 4 hours, and the glass was taken out after cooling to room temperature and washed with pure water for 5 times, and then dried at 120°C for 2 hours, and then allowed to stand at 600°C for 6 hours in a nitrogen atmosphere, and the glass was kept facing upward and placed in the cavity of a hydrogen plasma treatment instrument, and the vacuum pump was evacuated to a vacuum degree of 10Pa, and then hydrogen was introduced to a vacuum degree of 70Pa, and hydrogen plasma treatment was carried out. The hydrogen plasma treatment power was 200W, and the treatment time was 10 minutes to obtain modified glass;
[0049] (4) Electrostatic self-assembly: 5-vinylisophthalic acid, p-phenylenediamine, pure water and anhydrous ethanol were mixed in a mass ratio of 1:5:10:10, and then 0.03 times the mass of 5-vinylisophthalic acid carbodiimide was added. The mixture was stirred at 30°C and 1000 r / min for 2 h, and then allowed to stand at 40°C and 2 kPa for 8 h to obtain triphenylamide. Triphenylamide, triethoxysilane and n-hexane were mixed in a mass ratio of 1:2:10, and then 0.05 times the mass of triphenylamide divinyltetramethyldisiloxane platinum salt was added. The mixture was stirred and refluxed at 80°C and 800 r / min for 4 h, and then allowed to stand at 30°C and 2 kPa for 8 h. The mixture was placed for 3 hours to obtain triethoxy silane based on polyphenylamide; biphenyltetracarboxylic acid anhydride, ethyl 3,5-diaminobenzoate, triethoxy silane based on polyphenylamide and dimethylacetamide were uniformly mixed in a mass ratio of 5:2:2:50, stirred at 15°C and 1000r / min for 20 hours in a nitrogen atmosphere, and then 60% ethanol with a mass fraction of 50 times the mass of biphenyltetracarboxylic acid anhydride was added, and the mixture was stirred for 10 minutes to obtain a polyamic acid solution; the modified glass was immersed in the polyamic acid solution, ultrasonicated at 30°C and 40kHz for 20 minutes, washed with anhydrous ethanol 5 times, and dried at 70°C for 4 hours to obtain an electrostatic self-assembled glass;
[0050] (5) Vacuum impregnation: Vinyl trimethoxysilane, hydrochloric acid (mass fraction of 25-30%) and anhydrous ethanol were mixed in a mass ratio of 1:2:15, stirred at 30°C and 2000 r / min for 4 h, cooled to 5°C, filtered, washed with pure water and anhydrous ethanol 5 times each, dried at 70°C and 10 Pa for 6 h to obtain cage-type polysilsesquioxane; cage-type polysilsesquioxane and hydrogen-containing silicone oil were mixed in a mass ratio of 1:8, and chloroplatinic acid (0.005 times the mass of cage-type polysilsesquioxane) was added, stirred at 80°C and 800 r / min for 10 min, then heated to 110°C and stirred for 4 h, and then vinyl trimethoxysilane (3 times the mass of cage-type polysilsesquioxane) was added, the temperature was kept constant and stirred for 6 h, and then allowed to stand at 50°C and 2 kPa for 8 h to obtain modified cage-type polysilsesquioxane; the modified cage-type polysilsesquioxane was mixed in a mass ratio of 1:8, and then chloroplatinic acid (0.005 times the mass of cage-type polysilsesquioxane) was added, and the mixture was stirred at 80°C and 800 r / min for 10 min, then heated to 110°C and stirred for 4 h, then vinyl trimethoxysilane (3 times the mass of cage-type polysilsesquioxane) was added, the temperature was kept constant and stirred for 6 h, and then allowed to stand at 50°C and 2 kPa for 8 h to obtain modified cage-type polysilsesquioxane; Silsesquioxane, acetone and 80% ethanol by mass were mixed uniformly in a mass ratio of 1:6:6, stirred at 30°C and 500r / min for 2min to prepare an impregnation solution; the electrostatic self-assembled glass was immersed in a 10% hydrochloric acid solution by mass, ultrasonicated at 30°C and 40kHz for 8min, dried at -1°C and 10Pa for 6h, and then fixed in a vacuum impregnation machine with the assembled surface upward, and after the pressure was pumped to 10Pa, an impregnation solution 4 times the mass of the electrostatic self-assembled glass was added, and nitrogen was introduced to make the pressure reach 20kPa, and the assembled glass was allowed to stand at 20°C for 30min, and the assembled surface was rinsed with anhydrous ethanol and pure water for 5min respectively, dried at -10°C and 10Pa for 8h, allowed to stand at 150°C for 2h, allowed to stand at 250°C for 1h, allowed to stand at 400°C for 1h, and the heating rate was 3°C / min, and cooled to room temperature to obtain flexible glass.
[0051] Comparative Example 1
[0052] The preparation method of the flexible glass of Comparative Example 1 is different from that of Example 2 only in step (3). Step (3) is modified as follows: tetraethyl orthosilicate, anhydrous ethanol and pure water are uniformly mixed in a mass ratio of 1:5:5, stirred at 25°C and 40r / min for 2.5min to obtain a tetraethyl orthosilicate solution, and the tetraethyl orthosilicate solution is sprayed by a sprayer at a temperature of 0.06g / cm 2 The amount of the sprayed glass was sprayed on the surface of one side of the glass, and the glass was allowed to stand at 65°C for 35 minutes to obtain the sprayed glass; the sprayed surface of the sprayed glass was placed upward in the cavity of the hydrogen plasma treatment instrument, and the vacuum pump was evacuated to a vacuum degree of 8Pa, and then hydrogen was introduced to a vacuum degree of 75Pa, and hydrogen plasma treatment was performed. The hydrogen plasma treatment power was 150W, and the treatment time was 12 minutes to obtain the modified glass. The remaining steps were the same as in Example 2.
[0053] Comparative Example 2
[0054] The preparation method of the flexible glass of Comparative Example 2 is different from that of Example 2 only in step (3), and step (3) is modified as follows: Deposition and plasma treatment: Tetraethyl orthosilicate, anhydrous ethanol and pure water are mixed uniformly in a mass ratio of 1:5:5, stirred at 25°C and 40r / min for 2.5min to obtain a tetraethyl orthosilicate solution, and the tetraethyl orthosilicate solution is sprayed by a sprayer at a speed of 0.06g / cm 2 The amount of the sprayed glass was sprayed on one side of the glass surface, and the glass was allowed to stand at 65°C for 35 minutes to obtain the sprayed glass; the sprayed surface of the sprayed glass was fixed on the bottom of the container with the sprayed surface facing upward, and then nano titanium dioxide and potassium hydroxide with a mass fraction of 55% were mixed and added in a mass ratio of 1:7, and the distance from the liquid surface to the sprayed glass surface was 2.5 cm, and the reaction was carried out at 190°C for 4.5 hours, and after cooling to room temperature, the glass was taken out and washed with pure water for 4 times, and dried at 110°C for 2.5 hours to obtain the modified glass. The remaining steps were the same as in Example 2.
[0055] Comparative Example 3
[0056] The preparation method of the flexible glass of Comparative Example 3 is different from that of Example 2 only in step (4). Step (4) is modified as follows: 5-vinyl isophthalic acid, p-phenylenediamine, pure water and anhydrous ethanol are mixed uniformly in a mass ratio of 1:4.5:9:9, and then 0.02 times the mass of 5-vinyl isophthalic acid is added with carbodiimide, and the mixture is stirred at 25°C and 900 r / min for 2.5 h, and then allowed to stand at 35°C and 1.5 kPa for 9 h to obtain triphenylmethane amide; biphenyltetracarboxylic acid dianhydride, 3,5-diaminobenzene are mixed with diphenyltetracarboxylic acid dianhydride and 3,5-diaminobenzene. Ethyl benzoate, triphenylamide and dimethylacetamide were mixed uniformly in a mass ratio of 5:1.5:2.5:45, stirred at 10°C and 900 r / min for 22 hours in a nitrogen atmosphere, and then 55% ethanol with a mass fraction of 45 times that of biphenyltetracarboxylic dianhydride was added, and stirred for 12 minutes to obtain a polyamic acid solution; the modified glass was immersed in the polyamic acid solution, ultrasonicated at 25°C and 35kHz for 25 minutes, washed with anhydrous ethanol 4 times, and dried at 65°C for 5 hours to obtain an electrostatic self-assembled glass. The remaining steps were the same as in Example 2.
[0057] Comparative Example 4
[0058] The preparation method of the flexible glass of Comparative Example 4 is different from that of Example 2 only in step (5), and step (5) is modified as follows: vinyl trimethoxysilane, hydrochloric acid with a mass fraction of 28% and anhydrous ethanol are mixed uniformly in a mass ratio of 1:1.5:12, stirred at 25°C and 1800r / min for 5h, cooled to 3°C, filtered, washed with pure water and anhydrous ethanol 4 times each, dried at 65°C and 8Pa for 7h to obtain cage-type polysilsesquioxane; cage-type polysilsesquioxane, acetone and ethanol with a mass fraction of 75% are mixed uniformly in a mass ratio of 1:5:5, stirred at 25°C and 400r / min for 2.5min to prepare an impregnation solution; electrostatic The self-assembled glass was immersed in a hydrochloric acid solution with a mass fraction of 9%, ultrasonically treated at 25°C and 35kHz for 9 minutes, dried at -5°C and 5Pa for 7 hours, and then fixed in a vacuum impregnation machine with the assembled surface facing upward. After the pressure was reduced to 5Pa, an impregnation solution with a mass of 3.5 times that of the electrostatic self-assembled glass was added, and nitrogen was introduced to make the pressure reach 15kPa. The glass was allowed to stand at 15°C for 35 minutes, and the assembled surface was rinsed with anhydrous ethanol and pure water for 4 minutes respectively. The glass was dried at -8°C and 5Pa for 7 hours, allowed to stand at 145°C for 2.5 hours, allowed to stand at 230°C for 1.5 hours, and allowed to stand at 380°C for 1.5 hours. The heating rate was 2.5°C / min, and the glass was cooled to room temperature to obtain a flexible glass. The remaining steps were the same as those in Example 2.
[0059] Comparative Example 5
[0060] The preparation method of the flexible glass of Comparative Example 5 is different from that of Example 2 only in step (5), and step (5) is modified as follows: vinyl trimethoxy silane and hydrogenated silicone oil are uniformly mixed in a mass ratio of 2:7, and then 0.001 times the mass of chloroplatinic acid of the hydrogenated silicone oil is added, and the mixture is stirred at 75°C and 650 r / min for 12 min, and then the temperature is raised to 105°C and the stirring is continued for 5 h, and then vinyl trimethoxy silane of 1 times the mass of the hydrogenated silicone oil is added, and the temperature is kept constant and the stirring is continued for 5 h, and the mixture is allowed to stand at 45°C and 1.5 kPa for 9 h to obtain modified silicone oil; the modified silicone oil, acetone and 75% ethanol by mass are uniformly mixed in a mass ratio of 1:5:5, and the mixture is stirred at 25°C and 400 r / min for 2.5 m in, prepare an impregnation liquid; immerse the electrostatic self-assembled glass in a hydrochloric acid solution with a mass fraction of 9%, ultrasonically at 25°C and 35kHz for 9 minutes, dry at -5°C and 5Pa for 7 hours, and then fix it in a vacuum impregnation machine with the assembly surface facing up, pump the pressure to 5Pa, add an impregnation liquid 3.5 times the mass of the electrostatic self-assembled glass, and then introduce nitrogen to make the pressure reach 15kPa, stand at 15°C for 35 minutes, rinse the assembly surface with anhydrous ethanol and pure water for 4 minutes each, dry at -8°C and 5Pa for 7 hours, stand at 145°C for 2.5 hours, stand at 230°C for 1.5 hours, stand at 380°C for 1.5 hours, and heat up at a rate of 2.5°C / min. Cool to room temperature to obtain flexible glass. The remaining steps are the same as in Example 2.
[0061] Comparative Example 6
[0062] The preparation method of the flexible glass of Comparative Example 6 is different from that of Example 2 only in step (5). Step (5) is modified as follows: vinyl trimethoxy silane, hydrochloric acid with a mass fraction of 28% and anhydrous ethanol are mixed uniformly in a mass ratio of 1:1.5:12, stirred at 25°C and 1800r / min for 5h, cooled to 3°C, filtered, washed with pure water and anhydrous ethanol 4 times each, and dried at 65°C and 8Pa for 7h to obtain a cage-type polysilsesquioxane; the cage-type polysilsesquioxane and hydrogen-containing silicone oil are mixed uniformly in a mass ratio of 1:7, and then 0.004 times the mass of the cage-type polysilsesquioxane is added with chloroplatinic acid, stirred at 75°C and 650r / min for 12min, then heated to 105°C and continued to stir for 5h, and then 2.5 times the mass of the cage-type polysilsesquioxane is added with vinyl trimethoxy silane, and the temperature is kept constant. Continue stirring for 5 hours, stand at 45°C, 1.5kPa for 9 hours to obtain modified cage-type polysilsesquioxane; mix the modified cage-type polysilsesquioxane, acetone and 75% ethanol by mass in a mass ratio of 1:5:5, stir at 25°C, 400r / min for 2.5 minutes to prepare an impregnation solution; immerse the electrostatic self-assembled glass in a 9% hydrochloric acid solution by mass, ultrasonicate at 25°C, 35kHz for 9 minutes, dry at -5°C, 5Pa for 7 hours, and then fix it in a vacuum impregnation machine with the assembly surface facing upward, pump the pressure to 5Pa, add 3.5 times the mass of the electrostatic self-assembled glass impregnation solution, then introduce nitrogen to make the pressure reach 15kPa, stand at 15°C for 35 minutes, rinse the assembly surface with anhydrous ethanol and pure water for 4 minutes respectively, and dry at -8°C, 5Pa for 7 hours to obtain flexible glass. The remaining steps are the same as in Example 2.
[0063] Effect example
[0064] Table 1 below shows the performance analysis results of the UV protection, peeling resistance and impact resistance of the flexible glass of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.
[0065] Table 1
[0066]
[0067] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 6 in Table 1, it can be found that the flexible glass prepared by the present invention has good UV protection, peeling resistance and impact resistance.
[0068] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the transmittance of Examples 1, 2, and 3 is lower than that of Comparative Example 1, and the impact strength is higher, which indicates that the nano-titanium dioxide and potassium hydroxide react and deposit on the sprayed surface of the sprayed glass to form potassium titanate whiskers, which have the effect of strengthening and toughening the main body, and can absorb, reflect and scatter ultraviolet rays, thereby improving the ultraviolet protection and impact resistance of the flexible glass; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the peeling strength of Examples 1, 2, and 3 is higher than that of Comparative Example 2, which indicates that after the hydrogen plasma treatment, oxygen defects are generated on the treated glass surface, and the electrostatic self- During the assembly process, the surface of the modified glass is positively charged, and the negatively charged polyamic acid is adsorbed on the surface by electrostatic adsorption to form an electrostatic self-assembled layer, thereby improving the peeling resistance of the flexible glass; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the peeling strength of Examples 1, 2, 3 is higher than that of Comparative Example 3, which indicates that when polyphenylamide and triethoxysilane are reacted to synthesize a polyamic acid solution, the polyamic acid solution is combined with the surface of the modified glass during the electrostatic self-assembly process, and silicon hydroxyl groups are generated to form chemical bonds with the modified glass, thereby improving the peeling resistance of the flexible glass; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the peeling strength of Examples 1, 2 , 3 and comparative example 4 have higher peel strength and impact strength, which shows that the cage-type polysilsesquioxane is modified to form flexible side chains on the surface of the cage-type polysilsesquioxane, thereby increasing the fluidity of the cage-type polysilsesquioxane. The flexible side chains can combine with the hydrolyzed silanol groups on the electrostatic self-assembled layer to form a cross-linked network structure, increase the elasticity of the material, and fix the cage-type polysilsesquioxane in the overall structure as a stress node, thereby improving the peeling resistance and impact resistance of the flexible glass; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the impact strength of Examples 1, 2, 3 and Comparative Example 5 is higher, which shows that the use of modified cage-type polysilsesquioxane is superior to the use of modified As for silicone oil, the center point of the cage-type polysilsesquioxane in the modified cage-type polysilsesquioxane can be used as a stress node in the overall structure, thereby improving the impact resistance of the flexible glass; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6, it can be found that the transmittance of Examples 1, 2, 3 is lower than that of Comparative Example 6, and the peeling strength is high, which shows that the final multi-stage heat treatment to form polyimide increases the overall conjugated structure, makes it easier to absorb ultraviolet rays and form mobile electrons, thereby improving the ultraviolet protection of the flexible glass, and makes the free silicon hydroxyl groups react with each other to form silicon oxygen connections, making the overall structure more compact, thereby improving the peeling resistance of the flexible glass, and generating polyimide at the same time.
[0069] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing flexible glass, characterized in that: The flexible glass is prepared by slit-drawing and cutting glass liquid, reacting and depositing nano-titanium dioxide and potassium hydroxide, and plasma-treating the modified glass, electrostatically assembling the modified glass with polyamic acid, vacuum impregnating the modified cage-type polysilsesquioxane, and then performing multiple-stage heat treatment. The method for preparing the flexible glass comprises the following preparation steps: (1) Slit drawing: Silicon dioxide, aluminum oxide, magnesium oxide, calcium oxide, boron trioxide, strontium oxide, tin oxide and yttrium oxide are mixed evenly in a mass ratio of 90:20:3:1:2:2:0.3:1~120:30:5:3:4:3:0.5:3 and placed in a platinum crucible, and allowed to stand at 800~1000℃ for 15~20min, and then heated to 1600~1800℃ and allowed to stand for 2~3h to prepare glass liquid; the glass liquid is cooled to 1400~1450℃ and slit drawn, with the slit temperature of 1280~1300℃, the air temperature of 700~750℃, the slit width of 2~2.5mm, and the pulling speed of the draw-down of 15~25mm / s, and then allowed to stand at room temperature for 10~12h to obtain semi-finished glass; (2) Cutting and thinning: Soak the semi-finished glass in an acid solution for 3-5 minutes, take it out and wash it with pure water for 3-5 times, dry it at 60-70°C for 4-6 hours, and then cut it to the required size with a femtosecond laser. The femtosecond laser pulse width is 100-300fs. The cut semi-finished glass is suspended and soaked in an acid solution, and ultrasonicated at 20-30°C and 30-40kHz for 15-20 minutes. Take it out and wash it with pure water for 3-5 times, and dry it at 60-70°C for 4-6 hours to obtain glass. (3) Deposition and plasma treatment: The ethyl orthosilicate solution was sprayed at 0.05-0.08 g / cm 2 The amount of the sprayed glass was sprayed on the surface of one side of the glass, and the glass was allowed to stand at 60-70°C for 30-40 minutes to obtain the sprayed glass; the sprayed surface of the sprayed glass was fixed on the bottom of the container with the sprayed surface facing upward, and then nano titanium dioxide and potassium hydroxide with a mass fraction of 50-60% were mixed and evenly added in a mass ratio of 1:6-1:8, and the distance from the liquid surface to the sprayed glass surface was 2-3 cm, and the reaction was carried out at 180-200°C for 4-5 hours, and the glass was taken out after cooling to room temperature and washed with pure water for 3-5 times, and dried at 100-120°C for 2-3 hours, and then allowed to stand at 500-600°C for 6-8 hours in a nitrogen atmosphere, and the glass was placed in the cavity of a hydrogen plasma treatment instrument with the surface facing upward. The vacuum pump was evacuated to a vacuum degree of 5-10Pa, and then hydrogen was introduced to a vacuum degree of 70-80Pa, and hydrogen plasma treatment was carried out. The hydrogen plasma treatment power was 100-200W, and the treatment time was 10-15 minutes to obtain modified glass; (4) Electrostatic self-assembly: Biphenyltetracarboxylic acid anhydride, ethyl 3,5-diaminobenzoate, triphenylamide triethoxysilane and dimethylacetamide are uniformly mixed in a mass ratio of 5:1:3:40-5:2:2:50, stirred at 800-1000 r / min at 5-15°C for 20-24 hours in a nitrogen atmosphere, and then 50-60% ethanol with a mass fraction of 40-50 times the mass of biphenyltetracarboxylic acid anhydride is added, and stirring is continued for 10-15 minutes to obtain a polyamic acid solution; the modified glass is immersed in the polyamic acid solution, ultrasonicated at 20-30°C and 30-40kHz for 20-30 minutes, washed with anhydrous ethanol for 3-5 times, and dried at 60-70°C for 4-6 hours to obtain an electrostatic self-assembled glass; the preparation method of triphenylamide triethoxysilane is as follows: 5-vinylisophthalic acid, p-phenylenediamine, pure water and anhydrous ethanol are mixed evenly in a mass ratio of 1:4:8:8~1:5:10:10, and then 0.01~0.03 times the mass of 5-vinylisophthalic acid is added with carbodiimide, and the mixture is stirred at 20~30°C and 800~1000r / min for 2~3h, and then allowed to stand at 30~40°C and 1~2kPa for 8~10h to prepare triphenylamide; triphenylamide, triethoxysilane and n-hexane are mixed evenly in a mass ratio of 1:1:8~1:2:10, and then 0.03~0.05 times the mass of triphenylamide is added with divinyltetramethyldisiloxane platinum salt, and the mixture is stirred and refluxed at 70~80°C and 500~800r / min for 4~6h, and then allowed to stand at 20~30°C and 1~2kPa for 3~4h to prepare; (5) Vacuum impregnation: the modified cage-type polysilsesquioxane, acetone and 70-80% ethanol by mass are mixed uniformly in a mass ratio of 1:4:4-1:6:6, and stirred at 20-30°C and 300-500 r / min for 2-3 min to prepare an impregnation solution; The electrostatic self-assembled glass is immersed in a hydrochloric acid solution with a mass fraction of 8-10%, ultrasonically treated at 20-30°C and 30-40kHz for 8-10 minutes, dried at -10--1°C and 1-10Pa for 6-8 hours, and then fixed in a vacuum impregnation machine with the assembled surface facing upward, and after the pressure is reduced to 1-10Pa, an impregnation solution with a mass of 3-4 times of the electrostatic self-assembled glass is added, and nitrogen is introduced to make the pressure reach 10-20kPa, and the glass is allowed to stand at 10-20°C for 30-40 minutes, and the assembled surface is rinsed with anhydrous ethanol and pure water for 3-5 minutes respectively, and the glass is dried at -1--10°C and 1-10Pa for 6-8 hours, and the glass is allowed to stand at 140-150°C for 2-3 hours, and then subjected to multi-stage heat treatment to obtain flexible glass; the preparation method of the modified cage-type polysilsesquioxane is as follows: vinyltrimethoxysilane, hydrochloric acid with a mass fraction of 25-30%, and anhydrous ethanol are mixed in a mass ratio of 1:
1. The mixture was stirred at 1:1:10~1:2:15 for 4~6 hours at 20~30℃ and 1500~2000r / min, and then cooled to 1~5℃ and filtered. The mixture was washed with pure water and anhydrous ethanol for 3~5 times respectively, and dried at 60~70℃ and 5~10Pa for 6~8 hours to obtain cage-type polysilsesquioxane. The cage-type polysilsesquioxane and hydrogen-containing silicone oil were mixed at a mass ratio of 1:6~1:8, and then the cage-type polysilsesquioxane was added. Chloroplatinic acid with a mass of 0.003-0.005 times that of silsesquioxane is stirred at 70-80°C and 500-800 r / min for 10-15 min, then the temperature is raised to 100-110°C and stirring is continued for 4-6 h, then vinyltrimethoxysilane with a mass of 2-3 times that of cage-type polysilsesquioxane is added, the temperature is kept constant and stirring is continued for 4-6 h, and then the mixture is allowed to stand at 40-50°C and 1-2 kPa for 8-10 h to prepare the product.
2. The method for preparing flexible glass according to claim 1, characterized in that: The acid solution in step (2) is prepared by uniformly mixing hydrofluoric acid with a mass fraction of 6-10% and hydrochloric acid with a mass fraction of 15-25% in a mass ratio of 1:1-1:
2.
3. The method for preparing flexible glass according to claim 1, characterized in that: The tetraethyl orthosilicate solution in step (3) is prepared by uniformly mixing tetraethyl orthosilicate, anhydrous ethanol and pure water in a mass ratio of 1:4:4 to 1:6:6, and stirring at 20 to 30° C. and 300 to 500 r / min for 2 to 3 minutes.
4. The method for preparing flexible glass according to claim 1, characterized in that: The method of the multi-stage heat treatment in step (5) is: standing at 200-250°C for 1-2 hours, standing at 350-400°C for 1-2 hours, heating at a rate of 2-3°C / min, and cooling to room temperature.
Citation Information
Patent Citations
High-thermal-conductivity polyimide film prepared from core-shell structure heat-conducting filler and preparation method of film
CN110452418A
Flexible glass forming method and device
CN111453975A
Polyhedral oligomeric silsesquioxane modified acrylate-polyurethane composite material and preparation method thereof
CN111925483A
Preparation process of high-temperature-resistant strong cross film capable of preventing deformation of coated asphalt
CN114479138A